2013
DOI: 10.1080/17470919.2013.797020
|View full text |Cite
|
Sign up to set email alerts
|

The role of the eyes in processing an intact face and its scrambled image: A dense array ERP and low-resolution electromagnetic tomography (sLORETA) study

Abstract: The aim of the present study was to test whether the eyes of an intact face produced a specific brain response compared to the mouth, nose, or hair and whether their specificity was also maintained in a scrambled face. Fifteen subjects were asked to focus visual attention on global and single elements in intact faces and in their scrambled image. EEG data were recorded from 256-Hydrocel Geodesic Sensor-Net200. Event-related potentials (ERPs) analyses showed a difference between the intact face and the scramble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
2
16
1
Order By: Relevance
“…In contrast to former studies, we did not find any differences in N170 latency or amplitude between adolescents with and without ASD [42]. Although the N170 was right-lateralized in both groups as previously reported [17, 39], it is worthy to note that most studies employ natural faces and previous research suggests that intact natural faces and eyes result in greater and faster N170 responses [60], and schematic face stimuli might induce weaker neural responses [19]. The composition of Mooney stimuli mainly comprises black and white parts that create a 3D shape of a face [26].…”
Section: Discussioncontrasting
confidence: 71%
“…In contrast to former studies, we did not find any differences in N170 latency or amplitude between adolescents with and without ASD [42]. Although the N170 was right-lateralized in both groups as previously reported [17, 39], it is worthy to note that most studies employ natural faces and previous research suggests that intact natural faces and eyes result in greater and faster N170 responses [60], and schematic face stimuli might induce weaker neural responses [19]. The composition of Mooney stimuli mainly comprises black and white parts that create a 3D shape of a face [26].…”
Section: Discussioncontrasting
confidence: 71%
“…These findings suggest that face representations might significantly favour information around the eyes. The social importance of the eyes in a face context is indicated by the finding that the eyes are specifically informative when comprehending the nonverbal intentions of others, but only if inserted in an intact face [Cecchini et al 2013]. To preview our findings, eyes were more influential than any other face part for visual realism.…”
Section: Perception Of Eye Regionmentioning
confidence: 64%
“…Accordingly, Haxby et al (2000) reported that the superior temporal sulcus processes individual facial features, including the changeable aspects of faces and the perception of eye gaze. Moreover, Cecchini et al (2013) demonstrated that the left middle temporal gyrus (BA21) exhibits enhanced activation in response to eyes in an intact face condition than to eyes in a scrambled face condition. The results of the present study, in conjunction with the aforementioned findings, indicate that the role of the eyes in facial perception should be investigated with regard to other ERP components or using additional neuroimaging techniques.…”
Section: Discussionmentioning
confidence: 99%